Including relativistic and primordial non-Gaussianity contributions in cosmological simulations by modifying the initial conditions. Issue 3 (1st March 2022) - Enríquez, Miguel; Hidalgo, Juan Carlos; Valenzuela, Octavio
Abstract: We present a method to implement relativistic corrections to the evolution of dark matter structures in Newtonian simulations of a ΛCDM universe via the initial conditions. We take the nonlinear correspondence between the Lagrangian (Newtonian) evolution of dark matter inhomogeneities and the synchronous-comoving (relativistic) matter density description, and use it to promote the relativistic constraint as the initial condition for numerical simulations of structure formation. In this case, the incorporation of Primordial non-Gaussianity (PNG) contributions as initial conditions is straightforward. We implement the relativistic, f NL and g NL contributions as initial conditions for the L-PICOLA code, and compute the power spectrum and bispectrum of the evolved matter field. We focus specifically on the case of largest values of non-Gaussianity allowed at 1- σ by Planck observations ( f NL = −4.2 and g NL = −7000). As a checkup, we show consistency with the one-loop perturbative prescription and with a fully relativistic simulation (GRAMSES ) on the adequate scales. Our results confirm that both relativistic and PNG features are most prominent at very large scales and for squeezed triangulations. We discuss future prospects to probe these two contributions in the bispectrum of the matter density distribution.